Piano pedagogy and concert activity of A. Siloti in the context of musical education in the USA - Kulish, Mariya (Convergences - Journal of Research and Arts Education, 2023)
Since during the period of Soviet Union it was forbidden to study the activities of emigrants, purely scientific works dedicated to A. Siloti appeared only in 2000. Naturally, American scientists were the first to study the life and creative path of the artist. The purpose of the study is to reveal such key vectors of activity of the prominent representative of the Russian Diaspora A. Siloti during his stay in exile in the United States as a concert pianist and piano teacher. Due to the revolutionary events, he emigrated in 1919 first to Finland, then to France, Belgium and England, and finally stopped his search in the United States in 1921. In 1925 he began teaching at the Juilliard School of Music. Thus, the article reveals the circumstances under which the decision was made to emigrate, A. Siloti’s concert activities in the first years after moving to and his pedagogical style in Juilliard. Since the Juilliard School was one of the first institutions of higher music education in the United States in the early twentieth century, the key task of the study is to determine the role of A. Siloti in the history of music education.